Examining the relationship between schizotypy and religious experience among Irish adults. Issue 4 (21st April 2017) - Breslin, Michael J.; Lewis, Christopher Alan
ABSTRACT: The term schizotypy is used to describe a diverse range of characteristics symptomatic of schizotypal personality disorder and borderline personality disorder. An emerging body of research is concerned with the relationship between schizotypy and religiosity. Mixed findings suggest a gender-specific, weak positive association between schizotypy and religiosity. However, there has been little research on the relationship between schizotypy and religious experience. The present aim was to expand the literature on the relationship between schizotypy and religiosity by employing measures of religious experience. An opportunistic community-based sample of 371 Irish respondents completed the Measure of Prayer Experience, the M Scale short version, the Schizotypal Personality (STA), and Borderline Personality (STB) Scales. Multivariate multiple regression showed that age and Magical Thinking uniquely positively predicted both measures, while Impulsiveness uniquely negatively predicted the Measure of Prayer Experience only.